2008
DOI: 10.1002/cbm.675
|View full text |Cite
|
Sign up to set email alerts
|

Who stalks? A description of patients at a high security hospital with a history of stalking behaviour

Abstract: Although this small group of stalkers had been intrusive and attacking, few had been referred for treatment because of the stalking. The screening questionnaire is easy to use and can be done from records. It may be that such screening should become routine in specialist secure hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Cluster B disorders predominated among acquaintances and ex-intimates, while strangers had a much wider range of pathological personality traits. Although these findings need to be replicated using structured assessments, the prevalence of personality pathology is consistent with that reported in other clinical/forensic samples, at approximately 50% (Mullen et al, 1999;Rosenfeld and Harmon, 2002;Morrison, 2008;Whyte et al, 2008). Both this and Rosenfeld's (2003) study identified relatively high prevalence of personality disorder not otherwise specified diagnoses (PD NOS), suggesting that stalking behaviour may not be associated with a specific type of personality pathology but with combinations of traits across disorder categories.…”
Section: The Role Of Psychopathology In Stalking Behavioursupporting
confidence: 83%
“…Cluster B disorders predominated among acquaintances and ex-intimates, while strangers had a much wider range of pathological personality traits. Although these findings need to be replicated using structured assessments, the prevalence of personality pathology is consistent with that reported in other clinical/forensic samples, at approximately 50% (Mullen et al, 1999;Rosenfeld and Harmon, 2002;Morrison, 2008;Whyte et al, 2008). Both this and Rosenfeld's (2003) study identified relatively high prevalence of personality disorder not otherwise specified diagnoses (PD NOS), suggesting that stalking behaviour may not be associated with a specific type of personality pathology but with combinations of traits across disorder categories.…”
Section: The Role Of Psychopathology In Stalking Behavioursupporting
confidence: 83%
“…The typology has been used in a range of research demonstrating qualitative and quantitative differences in stalker behavior and outcomes between types (e.g., Binder, 2006; James et al, 2010; James & Farnham, 2003; MacKenzie, Mullen, Ogloff, McEwan, & James, 2008; McEwan, Mullen, & MacKenzie, 2009; McEwan & Strand, 2013; Morrison, 2007; Mullen, Pathé, & Purcell, 2001; Whyte, Petch, Penny, & Reiss, 2008). Given its integration into the SRP, the reliability with which stalkers can be classified into the typology will substantially influence the reliability of the SRP, but this has not been tested to date.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ex-intimate partners are at higher risk for both continued stalking (i.e., they usually stalk for longer periods of time than offenders who have never had an intimate relationship with the victim; Budd & Mattinson, 2000; Mohandie et al, 2006; Pathé & Mullen, 1997; Purcell, Pathé, & Mullen, 2002; Purcell et al, 2004; Rosenfeld, 2003; Tjaden & Thoennes, 1998), and are more often violent toward their victim (McEwan et al, 2009). Another robust risk factor for both renewed stalking and stalking-related violence is the presence of a personality disorder, and in particular cluster B disorders (i.e., Borderline and Antisocial; McEwan et al, 2008; Rosenfeld, 2003, 2004; Whyte, Petch, Penny, & Reiss, 2008). Stalking offenders whose behaviors persist and escalate into physical approach tend to be seeking intimacy or have a psychotic illness.…”
Section: Risk Factors For Stalking and Stalking-related Violencementioning
confidence: 99%